Introgresion del tamaño de la gluma y la cobertura del grano en poblaciones de sorgo - Alcala-Salinas, L.=700 1 Zavala-Garcia, F.; Montes-Garcia, M.; Castro-Navas, S.; Alvarado-Gomez, O.G.; Salinas-Garcia, G.E.
(Es, En)
Ilus., 29 ref.
Keywords: SORGHUM; FITOMEJORAMIENTO; HEREDABILIDAD; COSTA RICA; VARIANZA ADITIVA; AGRONOMIA MESOAMERICANA